Transthyretin familial amyloid polyneuropathy (TTR‐FAP): Parameters for early diagnosis. Issue 1 (19th December 2017) - Escolano‐Lozano, Fabiola; Barreiros, Ana Paula; Birklein, Frank; Geber, Christian
Abstract: Background: Familial transthyretin amyloidosis is a life‐threatening disease presenting with sensorimotor and autonomic polyneuropathy. Delayed diagnosis has a detrimental effect on treatment and prognosis. To facilitate diagnosis, we analyzed data patterns of patients with transthyretin familial amyloid polyneuropathy (TTR‐FAP) and compared them to polyneuropathies of different etiology for clinical and electrophysiological discriminators. Methods: Twenty‐four patients with TTR‐FAP and 48 patients with diabetic polyneuropathy (dPNP) were investigated (neurological impairment score NIS; neurological disability score NDS) in a cross‐sectional design. Both groups were matched for gender and presence of pain. Quantitative sensory testing (QST), sympathetic skin response (SSR), heart rate variability (HRV), and nerve conduction studies (NCV) were performed. Both groups were compared using univariate analysis. In a stepwise discriminant analysis, discriminators between both neuropathies were identified. These discriminators were validated comparing TTR‐FAP patients with a cohort of patients with chemotherapy‐induced polyneuropathy (CIN) and chronic inflammatory demyelinating neuropathy (CIDP). Results: TTR‐FAP patients scored higher in NDS and NIS and had impaired cold detection (CDT, p = .024), cold–warm discrimination (TSL, p = .019) and mechanical hyperalgesia (MPT, p = .029) at the hands, SSR (upper limb, p = .022) HRV and ulnar and sural NCS (all p < .05) were more affected in TTR‐FAP. Ulnar nerve sensory NCV, CDT, and the MPT but not the other parameters discriminated TTR‐FAP from dPNP (82% of cases), from CIN (86.7%) and from CIDP (68%; only ulnar sNCV). Conclusion: Low ulnar SNCV, impaired cold perception, and mechanical hyperalgesia at the hands seem to characterize TTR‐FAP and might help to differentiate from other polyneuropathies. Abstract : Twenty‐four patients with TTR‐FAP and 48 patients with diabetic polyneuropathy (dPNP) were clinically and electrophysiologically investigated. We found differences in the cold detection, cold–warm discrimination, mechanical hyperalgesia, and SSR amplitude in the hands, as well as in the nerve conduction velocities of the sensory ulnar and sural nerves (TTR‐FAP more affected). Ulnar nerve sensory NCV, CDT, and the MPT discriminated TTR‐FAP from dPNP (82% of cases). These results were confirmed on a cohort of chemotherapy‐induced polyneuropathy (86%) and in a cohort of CIDP (68%).